Analysis Of The Influence Of Tourism Attraction On Domestic Tourist Visits To Tourism Attractions In Ciwidey - Dwi Meisha Auliyaa; Najmah Chairunisa Pohan (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
Tourism is an important sector in the economic development of a region, with tourist attractions being a key factor in attracting visitor arrivals. This study aims to analyze the influence of tourist attractions on domestic tourist visits to tourist destinations in Ciwidey, Bandung Regency. A qualitative approach was used with data collection techniques consisting of in-depth interviews and participatory observation with domestic tourists visiting Ciwidey. The results show that natural beauty, cultural uniqueness, and a variety of tourist activities are the main attractions in Ciwidey. These findings provide valuable insights for the development of tourism in Ciwidey, including preserving natural beauty, expanding tourist activity variations, and addressing challenges related to infrastructure and visitor management.